Upscale production of instant coconut milk-based rice porridge with corn (Guinataang mais) - Arcilla, Vladimira Fe Casabar; Azanza, Ma. Patricia V. (2000.)
ABSTRACT This study worked on the scaling up of the production of the instant guinataang mais developed by Umali (1999). This study was part of the UP-Philrice research study entitled "Rice and Rice-Based Disaster Foods". Consumer acceptance, quality assessment and cost analysis of the product were also determined. Phase I dealt with the upscale production of the instant rice and corn. The steps in producing the instant rice included hydration, gelatinization, dehydration and puffing. Hydration of rice kernels was done by soaking rice in 0.5% CaCl2 solution at 50°C for 5 min. The gelatinized grains were dehydrated using a convective air dryer set at 55°C until moisture content of 8-10% was achieved for500 g, 90 minutes was adequate to attain the desired moisture content, while for 1000 g level of production, 105 mins was required. The oil immersion was used to puff 100 g of dehydrated rice for 1 sec at 210°C. Scaling up instant corn production involved blanching, soaking and dehydration of the corn kernels in a convective air dryer. The kernels were blanched in boiling water for 3 mins. and soaked in 10% lye solution at 65°C for 3 min. One hundred g of corn was dried for 205 min while 500 g was dried for 235 min both at 55°C. Phase II dealt with product modification of the instant guinataang mais. The conventionally-cooked recipe was presented with the rehydrated modified instant product for sensory evaluation. Results of paired comparison tst have shown that the conventional recipe was significantly different at 5% significance level with the modified instant product in all sensory attributes except rice texture and consistency description. The re-modified instant product was also presented for sensory evaluation. Statistical analyses were done to determine differences between the three formulations of guinataang mais: conventionally cooked, modified and re-modified instant guinatang mais. Analysis of Variance and DMRT results at 5% level of significance indicated that the re-modified instant product was not significantly different with the conventionally prepared recipe in all sensory attributes except consistency and aroma acceptability. The re-modified instant product was also not significantly different with the modified formulation in all sensory attributes except rice base color and consistency. Furthermore, the 3 formulations were significantly different from each other in terms of the overall flavor acceptability. Phase III of this study determined the physicochemical and microbiological characteristics of the instant product. Aw value of the compounded instant mix was 0.422 while the rehydrated product had an Aw of 0.978. For the compounded and rehydrated product, mean pH values were 6.32 and 6.61 respectively. The microbiological test done were total plate count using Plate Count Agar and yeast and mold count using acidified Potato Dextrose Agar. Total plate count of compounded product was 10 to 3 cfu/g. The rehydrated product had a total plate count of 10 to 4 and a yeast and mold count of 10 to 3 cfu/g. The cost per 75 g dired serving portion of instant guinataan mais, which is approximately 250ml upon rehydration, was computed at P11.89 with 10% mark up. It was cheaper by P4.36 when compared with the commercially available instant product with the same serving portion. Further studies on the shelf life of the product and an appropriate packaging material is recommended. Pilot scale production and improvement of corn texture by using other processing methods are also recommended.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Porridge